Heterotopic Ossification in Primary Total Hip Arthroplasty: which is the role of drainage? - Di Benedetto, Paolo; Zangari, Andrea; Magnanelli, Stefano; Cainero, Vanni; Beltrame, Alessandro; Gisonni, Renato; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The Heterotopic Ossification (HO) is a common complication following Total Hip Arthroplasty (THA). Although there is no concordance in Literature regarding the etiopathogenic mechanism, various HO risk factors have been recognized, both related to the patient and associated with the surgical procedureLiterature does not consider the use of intra-articular drainage as a possible risk factor. Our hypothesis is that this item can contribute to the development of HO. Materials and Methods: 425 implants of hip arthroplasty performed between 2014 and 2017 at the Ortopedic Clinic of Udine were included in the study. No patient performed pre-operative or post-operative anti-HO prophylaxis during follow-up. Radiographs of preoperative and postoperative at 1 year were analyzed according to the Brooker Classification. Results: The incidence of HO in patients with intra-articular drainage is 24.6%, while the incidence of HO in patients without intra-articular drainage is 15.3%, with a statistically significant difference. Conclusions: The data obtained suggest to consider the use of intra-articular drainage as a possible intra-operative risk factor for HO. This is a retrospective cohort study, so we need more studies and more robust experimental designs to confirm these results.